Annual changes in the prevalence of asthma may be related to air pollution in Fukuoka: 29 years of observation. Issue 2 (29th June 2020) - Odajima, Hiroshi; Kawano, Toshiaki; Wakatsuki, Masatoshi; Akaminea, Yuko; Okabe, Koki; Oki, Tuyoshi; Matsuzaki, Hiroshi; Murakami, Yoko; Iwata, Mihoko; Taba, Naohiko; Motomura, Chikako; Honjo, Satoshi; et al.
The relationship between the annual changes of the prevalence of bronchial asthma (BA) and that of concentrations of air pollutants has not been reported. We studied the annual prevalence of BA, remission of BA, and wheeze in children at the same five elementary schools in Fukuoka city, Japan, in October to November from 1988 to 2016 by the same methods using the same questionnaire. Annual changes in the prevalence of asthma among boys were related to changes in the air concentrations of NO (r=0.708), NO2 (r=0.665) suspended particulate matter (SPM) (r=0.803), and smoking rate (r=0.741), but there were no such relationships among girls. Annual changes in the prevalence of wheeze were related to changes of NO, NO2, SPM, and smoking rate among boys and girls (NO: r=0.650, 0.660; NO2 : r=0.556, 0.490; SPM: r=0.582, 0.518; smoking rate: r=0.656, 0.593, respectively) (all of the above are significant with p<0.05). There was no relationship between remission of BA and any of the pollutants. Annual changes in the prevalence of boys' BA and boys' and girls' wheeze among first-grade children (age 6 or 7 years) in Fukuoka were correlated with changes in the concentration of air pollutants (SPM, NO, NO2 or smoking rate). Recent decrease of asthma prevalence in this area might be related to the decreasing tendency of air pollutant concentration. The causal relationship between the two will need to be verified in the future Annual changes in the prevalence of child asthma in Fukuoka are correlated with those in the concentration of air pollutants (SPM, etc. ). A recent decrease of asthma prevalence might be related to the decreasing concentration of air pollutants. https://bit.ly/2RlYXfu